Two new species of Monopisthocotyla (Dactylogyridea: Dactylogyridae) parasitizing the nasal cavities of Bryconops melanurus (Characiformes: Iguanodectidae) from coastal drainages of the Eastern Amazon, Brazil - Santos-Neto, João F.; Paixão, Saymon M.; Domingues, Marcus V. (Zootaxa, 2024)
The present study integrates molecular and morphological data to support the proposal of new species of Telethecium Kritsky, Van Every & Boeger, 1996 and Diaphorocleidus Jogunoori, Kritsky & Venkatanarasaiah, 2004 from the nasal cavities of Bryconops melanurus (Bloch) of the coastal drainages of the Eastern Amazon. Telethecium tiquira sp. n. is characterized by possessing a male copulatory organ (MCO) with two circular sclerotized brims on the base, a coiled tubular shaft having 1 ½ counterclockwise rings, an accessory piece with enlarged base, pincer-shaped at the distal portion; a sclerotized calyx-shaped vaginal vestibule, and hooks with proximal shank dilatation comprising 3/4 of the shank length. Also, Telethecium tiquira sp. n. can be easily distinguished from other species of the genus by the absence of a protruding bag located at the level of the copulatory complex. Diaphorocleidus forficata sp. n. is characterized by having a MCO with two counterclockwise rings, circular sclerotized tandem brim associated with the base of the MCO; accessory piece non-articulated with the MCO, bifurcate, pincer-shaped; vaginal pore sinistral-ventral with opening marginal, vaginal canal sclerotized, elongated, comprising one loop in the proximal portion before entering to the seminal receptacle; ventral anchor with shaft elongated and evenly curved on the axis; point short and slightly curved, and hooks similar in shape and size, hooks with proximal dilatation comprising approximately ½ of the shank length. Furthermore, D. forficata sp. n. is supported by phylogenetic analysis based on sequences of the partial 28S rDNA gene, which placed D. forficata sp. n. in a well-supported clade of Diaphorocleidus spp. of characiform fishes. Thus, the two new species described here expand our knowledge about the diversity of monopisthocotylan parasites from the nasal cavities of Neotropical fishes. The findings of this study provide valuable insights into the biodiversity of the region and highlight the importance of further research in this area.